Estrogen-related receptor-α (ERRα) deficiency in skeletal muscle impairs regeneration in response to injury - LaBarge, Samuel (Federation of American Societies for Experimental Biology, 2014)
The estrogen-related receptor-α (ERRα) regulates mitochondrial biogenesis and glucose and fatty acid oxidation during differentiation in skeletal myocytes. However, whether ERRα controls metabolic remodeling during skeletal muscle regeneration in vivo is unknown. We characterized the time course of skeletal muscle regeneration in wild-type (M-ERRαWT) and muscle-specific ERRα(−/−) (M-ERRα(−/−)) mice after injury by intramuscular cardiotoxin injection. M-ERRα(−/−) mice exhibited impaired regeneration characterized by smaller myofibers with increased centrally localized nuclei and reduced mitochondrial density and cytochrome oxidase and citrate synthase activities relative to M-ERRαWT. Transcript levels of mitochondrial transcription factor A, nuclear respiratory factor-2a, and peroxisome proliferator-activated receptor (PPAR)-γ coactivator (PGC)-1β, were downregulated in the M-ERRα(−/−) muscles at the onset of myogenesis. Furthermore, coincident with delayed myofiber recovery, we observed reduced muscle ATP content (−45% vs. M-ERRαWT) and enhanced AMP-activated protein kinase (AMPK) activation in M-ERRα(−/−) muscle. We subsequently demonstrated that pharmacologic postinjury AMPK activation was sufficient to delay muscle regeneration in WT mice. AMPK activation induced ERRα transcript expression in M-ERRαWT muscle and in C2C12 myotubes through induction of the Esrra promoter, indicating that ERRα may control gene regulation downstream of the AMPK pathway. Collectively, these results suggest that ERRα deficiency during muscle regeneration impairs recovery of mitochondrial energetic capacity and perturbs AMPK activity, resulting in delayed myofiber repair.—LaBarge, S., McDonald, M., Smith-Powell, L., Auwerx, J., Huss, J. M. Estrogen-related receptor-α (ERRα) deficiency in skeletal muscle impairs regeneration in response to injury.